A reconstruction of the North Atlantic since the earliest Jurassic. (14th September 2016) - Barnett‐Moore, Nicholas; Müller, Dietmar R.; Williams, Simon; Skogseid, Jakob; Seton, Maria
Abstract: The stretched continental margins of the North Atlantic region record a plate kinematic history dominated by major episodes of extension since the Late Palaeozoic. Accounting for the restoration of this stretched continental crust across the region, and the subsequent derivation of plausible full‐fit configurations between these continents, prior to extension, still remains unresolved. Previous plate reconstructions have highlighted difficulties such as determining the amount of extension to be distributed across the multiple episodes of rifting, or defining the distribution of extension across intraplate deformation occurring adjacent to the rifting of two major continents. Here, we implement a new approach to derive a set of total reconstruction poles based on a full‐fit, palinspastic restoration of the conjugate margins that considers the rifting evolution of the North Atlantic in a regional plate kinematic context since the Earliest Jurassic. Gravity inversion forms the basis of our regional crustal thickness estimates, and aids in the identification of thinned continental crust. Our crustal restoration estimates are computed in multiple phases along margin segments in accordance with the timing of their major rifting episodes. Our model predicts a full‐fit, prerift, palaeogeographic position of all the major continents across the North Atlantic; and predicts a time‐dependent evolution of multiple phases of extension including regional divergence directions, consistent with previous observations. Our plate model represents a new approach to plate kinematic reconstructions incorporating the application of a multiphase restoration methodology applied in a major regional context, constrained by the synthesis of several different geological and geophysical data sets.